MANAGEMENT TOURISM DESTINATION PUAK BEACH DUMAI CITY - Rahmad Rafi; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Management (Management) is the science and art of regulating the process of utilizing human resources and other sources effectively and efficiently to achieve a certain destination, so as to increase tourist arrivals in these attractions. This study aims to determine the management of Puai Beach Attraction in Dumai City. This study uses qualitative methods to examine the issues raised. The key informants used in this study were 5 people, taken using interview techniques. While the data collection techniques in this study used observation, interviews, documentation. By using sub-variables which in Management (Terry, 1958) are divided into planning, organizing, mobilizing, and controlling. From the results of research conducted in the field with research on the management of the Puai Beach Tourism Object Dumai City shows that 1) the planning carried out by Puak Beach is in accordance with the work program; 2) Supervision conducted by the Role of Service; 3) Movements including those that have met the needs or not; 4) Organizing by always holding meetings at the end of the month, including in good condition.